Solvent dependent fabrication of bifunctional nanoparticles and nanostructured thin films by self assembly of organosilanes - Pandey P.C.; Shukla S. (My University, 2025)
Designing the self-configured framework of nanoporous lattices, to assemble bifunctional nanomaterials on solid substrates, retaining the well-defined nanogeometry is the chief objectives of the present study. Organofunctionalised alkoxysilanes (3-aminopropyltrimethoxysilane (APTMS), 2-(3, 4-epoxycyclohexyl) ethyltrimethoxysilane (EETMS)) containing the functional groups, amino, epoxy, hydroxyl etc., are the potential candidates for the fabrication of nanostructured and monolayered assembly of mono (PdNPs) and bimetallic (Au@PdNPs, Ag@PdNPs) nanomaterials, via sol–gel processing, in aqueous and non-aqueous media with thickness in the range 6–8 nm. The interactions between the silane coupling agents are studied using dynamic light scattering (DLS) technique. The range of hydrodynamic radii (RH) in different solvents is attributed to the multistage directional alignment of colloidal solutions of alkoxysilane functionalized nanomaterials on solid substrates. The difference in the tendency of the formation of aggregate structures is a function of solvent, critical micelle concentration (CMC) of the surfactant. 2-propanol based colloidal dispersions of nanoparticles are exceptionally more homogenously dispersed and have relatively lower z-average values, as the possibility of cluster formation is reduced. The micellar behavior of APTMS and reactivity of EETMS directs the formulation of the stable and catalytically dynamic nanomaterials. The sensitivity of monolayer deposition lies with the water content of the micellar solution, therefore uniform coating is promised by employing nonaqueous solvents (0.66 nm) which tend to slowdown the rate of condensation. Pore diameter and overall architecture are achieved due to less branched structures of the EETMS and APTMS, which are acting as scaffolds for thin film fabrication, and relative rates of evaporation of solvents. [Figure not available: see fulltext.]. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.